2019
DOI: 10.3889/oamjms.2019.378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anterior Chamber Depth and Anterior Chamber Angle Changing After Phacoemulsification in the Primary Angle Close Suspect Eyes

Abstract: BACKGROUND: Phacoemulsification surgery has the ability to deeply alter the segment anterior morphology, especially in eye with shallow anterior chamber (AC), narrow anterior chamber angle (ACA). However, the changes of anterior chamber depth (ACD) and ACA on the close angle suspect eyes after phacoemulsification have not been mentioned in many studies. So, we conduct this research. AIM: To evaluate the alteration in the ACA and ACD after phacoemulsification in the close angle suspect eyes. METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“… 24 Another study demonstrated approximately 2 times increases in ACA indicators, including AOD-500, AOD-750, TISA-500, and TISA-750 following cataract surgery. 25 This was similar to the results of another study, concluding the change of the ACA parameters after cataract extraction of the patients with angle-closure glaucoma. 26 Similarly, our results represented an increasing tendency in ACA measurements following phacoemulsification procedure in both diabetic and nondiabetic patients.…”
Section: Discussionsupporting
confidence: 90%
“… 24 Another study demonstrated approximately 2 times increases in ACA indicators, including AOD-500, AOD-750, TISA-500, and TISA-750 following cataract surgery. 25 This was similar to the results of another study, concluding the change of the ACA parameters after cataract extraction of the patients with angle-closure glaucoma. 26 Similarly, our results represented an increasing tendency in ACA measurements following phacoemulsification procedure in both diabetic and nondiabetic patients.…”
Section: Discussionsupporting
confidence: 90%
“…The iridocorneal angle is an important component in determining the diagnosis of glaucoma (Rufer, 2010). In postoperative patients, widening of the iridocorneal angle and decreased intraocular pressure are conditions that are often encountered both in patients with glaucoma disorders and in patients with normal eye conditions (Altan, 2004) implants whose thickness is thinner, the iris will be located further back which will then widen the anterior chamber and the irido-corneal angle (Vu et al, 2019). Another study reported that the preoperative convex iris shape changes to a flat shape after cataract extraction due to posterior movement of the iris with an increase in anterior chamber depth and also posterior displacement of the iris base after lens removal causes widening of the iridocorneal angle (Hussein et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the inspection characteristics of UBM and gonioscopy at early years, some more detailed parameters could not be investigated [19,[21][22]24] . Further studies have been carried out to explore the changes of the angle structure of the anterior chamber after phacoemulsification by AS-OCT [3,[6][7][10][11]26] . It has the advantage of allowing faster the anterior chamber cross-sectional imaging than UBM, without contacting with the eyeball.…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
“…Clear-lens extraction was more effective and cost-effective than LPI and should be an option for first-line treatment for primary angle-closure glaucoma (PACG). Current researches showed that cataract surgery with intraocular lens (IOL) implantation can deepen the anterior chamber and increase the width of the anterior chamber angles [2][3][4][5][6][7] . The effect of cataract surgery on IOP in glaucoma patients has been reported in many studies of different subtypes of glaucoma.…”
Section: Introductionmentioning
confidence: 99%